Removing Edge Defect In Color-Based Image Retrieval. - Sumari, Putra; Vili, Mala; Kamarulhaili, Hailiza; Salam, Rosalina Abdul (2004)
Growth of digital image archive is increasing rapidly and the demand for effective and efficient tools for searching through large amounts of visual data is great. One of the contributing factors toward an efficient tool is the quality of images being handle.